Serum Calprotectin Levels in Dogs with Diarrhea - Simsek, Aynur; Kochan, Akin; Yesilmen Alp, Simten; Sayin Ipek, Duygu Neval; Icen, Hasan (Acta Scientiae Veterinariae, 2022)
Background: Diarrhea induced by infectious factors may lead to significant health problems in dogs. Canine parvovirus (CPV), canine coronavirus (CCV), canine distemper virus (CDV), Giardia spp., Escherichia coli (E. coli), and Salmonella spp. are the important infectious agents that may induce diarrhea in dogs. The present study aimed to investigate the effect of CPV, CCV, CDV, Giardia spp., E. coli, and Salmonella spp. infections on the change in serum calprotectin (Calp) concentration. Materials, Methods & Results: A total of 30 dogs were enrolled in the study. The study dogs were divided into 3 groups. Healthy animals as confirmed by clinical examination and animals negative for the specified pathogens were placed in Group 1. Animals infected by one or more agents, including CPV, CCV, CDV, and Giardia spp., but negative for E. coli or Salmonella spp. were placed in Group 2. Finally, animals positive for E. coli or Salmonella spp. and infected or not infected by one or more agents, including CPV, CCV, CDV, and Giardia spp., were placed in Group 3. Stool samples and rectal and conjunctival swab samples were collected to investigate the etiologic agents that induced diarrhea. Blood samples were collected through vena cephalica antebrachii for hematological and biochemical examinations. The samples were obtained via routine clinical examinations at the Prof. Dr. Servet SEKİN outpatient clinic at Dicle University Veterinary Faculty. CPV, CCV, CDV, and Giardia spp. diagnoses were made based on immunochromatographic test kits. The bacteriological analysis of stool samples were used to diagnose E. coli and Salmonella spp. infection. Serum Calp concentrations were measured by Enzyme-Linked Immunosorbent Assay (ELISA). The analysis of swab and stool samples by immunochromatographic rapid diagnosis kits and microbiological methods showed that 5 animals were infected with CPV, 10 with CCV, 6 with CDV, 3 with Giardia spp., 12 with E. coli, and 2 with none of the specified agents. Total leukocyte count (WBC), lymphocyte (Lym) (%), and granulocyte (Gra) (%) values were higher in the diarrheal dogs when compared with the control group. In the biochemical examination of serum samples, TBIL and P levels were higher and Na levels were lower in Group 3 when compared to the control group (P = 0.025, 0.024, and 0.018, respectively). TP and Alb values were lower in Group 2 compared to Groups 1 and 3 (P = 0.001 and 0.019 for TP, P = 0.000 and 0.001 for Alb, respectively). There was a statistically significant difference in CK levels between Group 1 and Group 2 (P = 0.013). Serum Calp level was higher in the E. coli infected group (Group 3) compared to the other groups, no significant differences were noted between the groups (P > 0.05). Discussion: In conclusion, to the best of authors knowledge, this study is the first to evaluate serum Calp levels in dogs with diarrhea induced by viral, bacterial, and protozoan infections. The Calp level was higher in the sick dogs that were infected by at least one agent, including CPV, CCV, CDV, and Giardia spp., and were at the same time E. coli positive when compared with the control group and the group without E. coli infections. It was concluded that new studies could be useful to reveal the diagnostic importance of serum Calp concentration in dogs with diarrhea and that these results may contribute to future studies in this area. Keywords: calprotectin, diarrhea, dog, serum.